Acute Heterogeneous Changes in Muscle and Tendon Viscoelastic Properties Following a VO₂max Treadmill Test in High-Level Male Soccer Players - Karol Skotniczny; Artur Terbalyan; Michał Krzysztofik; Robert Roczniok; Miłosz Drozd; Łukasz Radzimiński; Jakub Jarosz (Applied Sciences)
Background: This study aimed to investigate the acute changes in muscle and tendon viscoelastic properties in response to a progressive treadmill VO2max test among professional male soccer players. Methods: Bilateral assessments at five sites—the Achilles tendon (AT), biceps femoris, semitendinosus, rectus femoris (RF), and sternocleidomastoid (SCM)—measured tone (oscillation frequency), dynamic stiffness, logarithmic decrement (elasticity), stress relaxation time, and creep. Each site was probed five times and values averaged. Repeated-measures ANOVA (Time × Side) with Bonferroni correction tested pre- to post-exercise changes; Pearson’s r examined associations with VO2max. Results: Significant Time effects (all p < 0.05) were observed for RF frequency (ηp2 = 0.226), RF creep (ηp2 = 0.144), AT stiffness (ηp2 ≈ 0.035), AT frequency (ηp2 = 0.035), and SCM frequency (ηp2 = 0.037). Post-exercise, right AT stiffness fell by 65 ± 14 N/m (p = 0.015), while left AT stiffness rose by 22 ± 9 N/m (p = 0.015). RF stiffness decreased by 28 ± 6 N/m (p < 0.001) and tone by 1.2 ± 0.3 Hz (p < 0.001), with creep (+0.08 ± 0.02; p < 0.001) and relaxation time (+1.5 ± 0.7 ms; p < 0.001) increasing. SCM tone declined by 0.8 ± 0.4 Hz (p = 0.010). Baseline RF properties—frequency (r = −0.597), stiffness (r = −0.59), relaxation time (r = 0.53), and creep (r = 0.48)—correlated moderately with VO2max (all p < 0.05). Conclusions: These findings suggest that viscoelastic adaptations to exhaustive aerobic exercise are tissue- and side-specific, and that rectus femoris viscoelastic properties may serve as potential indicators of endurance readiness.